2013
DOI: 10.1136/sextrans-2013-051184.0728
|View full text |Cite
|
Sign up to set email alerts
|

P3.272 Prevalence of Chlamydia Trachomatis, Neisseria Gonorrhoeae and Ureaplasma Urealyticum in Pregnant Women of Sabzevar - Iran

Abstract: Objectives Antimicrobial resistance in Neisseria gonorrhoeae is a major public health problem worldwide. Slovenia is among the countries with highest prevalence of decreased susceptibility and resistance to extended-spectrum cephalosporins (ESCs) in Europe. Herein, the phenotypic and molecular characterization of Slovenian N. gonorrhoeae strains from 2008-2012 is presented. Methods N. gonorrhoeae isolates cultured [2008][2009][2010][2011][2012] in Slovenia (n = 138) were examined for antimicrobial susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
2
10
1
1
Order By: Relevance
“…The prevalence estimate of genital N. gonorrhoeae infection in the present study (1.6%) was comparable to the recently reported prevalence of 1.3% and 1.2% among pregnant women of Shiraz and Sabzevar (North-East of Iran) cities (21,22). However, no neonates with ocular N. gonorrhoeae infection were identified in this study.…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence estimate of genital N. gonorrhoeae infection in the present study (1.6%) was comparable to the recently reported prevalence of 1.3% and 1.2% among pregnant women of Shiraz and Sabzevar (North-East of Iran) cities (21,22). However, no neonates with ocular N. gonorrhoeae infection were identified in this study.…”
Section: Discussionsupporting
confidence: 85%
“…In pregnant women, the prevalence of C. trachomatis has been reported from 1% in Saudi Arabia to 13.6% in Iraq (23)(24)(25)(26). In Iran, the isolation of C. trachomatis from various regions was reported to range from 2.9% to 13.7% (8,(27)(28)(29). The frequency of C. trachomatis in this study was 10.52%, which is in line with the reported range of isolation from our country.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, the isolation frequency of C. trachomatis was reported to be up to 23% in pregnant women (7,8) and about 11% -13% in women with abortion (7)(8)(9). Among other causative agents of STDs, there are Mycoplasma spp.…”
Section: Introductionmentioning
confidence: 99%
“…These studies reported a prevalence of 9.3% to 34.71% for chlamydia infection (14)(15)(16)(17)(18)(19)(20)(21). A study on 196 pregnant women attending maternal hospitals in Central Iran revealed a prevalence of 14.79% for chlamydia infection (22). The global estimate for the prevalence of chlamydia among women in 2005 reported by the WHO was 3.53% (23).…”
Section: Prevalence Of Stis In Iranmentioning
confidence: 99%